Lumbar to sacral root rerouting to restore bladder function in a feline spinal cord injury model: Urodynamic and retrograde nerve tracing results from a pilot study. Issue 1 (4th January 2018) - Lam Van Ba, Ornella; Barbe, Mary F.; Caremel, Romain; Aharony, Shachar; Loutochin, Oleg; Jacques, Line; Wood, Matthew W.; Tiwari, Ekta; Tuite, Gerald F.; Campeau, Lysanne; Corcos, Jacques; Ruggieri, Michael R.
Abstract : Aims: Lumbar to sacral rerouting surgery can potentially allow voiding via a skin‐central nervous system‐bladder reflex pathway. Here, we assessed if this surgery was effective in treating neurogenic bladder dysfunction/sphincter in felines. Methods: Eight cats underwent spinal cord transection (SCT) at thoracic level 10/11. Unilateral L7 to S1 ventral root anastomosis was performed 1 month later in six cats. Two cats served as transection‐only controls. Electrical and manual stimulation of L6‐S1 dermatomes, and urodynamics were performed at 3, 5, 7, and 9/10 months post transection. At 9/10 months, cats were also evaluated by direct electrophysiological testing of anastomosed roots with urodynamics, then tissue collection and examination of the root anastomosis site and lumbosacral cord ventral horns for cells retrogradely labeled from tracer dye injected 2 weeks earlier into the bladder wall. Results: At 9/10 months, four of six rerouted cats exhibited increased detrusor pressure provoked by cutaneous stimulation, one cat bilaterally. Two cats presented with a voiding stream after ipsilateral cutaneous stimulation at 7 and 9 months. All six rerouted animals showed regrowth of axons from the L7 ventral horn to the bladder, although some aberrant axonal regrowth was also observed. Conclusion: L7 to S1 ventral root rerouting below the level of SCT showed successful axonal regrowth to the bladder from the L7 spinal cord segment in all rerouted animals, and induced increased detrusor pressure response to cutaneous stimulation in a subset. This feasibility study paves the way for future animal studies for bladder reinnervation.